THE CORRELATION OF STUDENTS’ MOTIVATION AND ENGLISH LEARNING ACHIEVEMENT - Eki Saputra; agnes zayananda putri; Dian Susyla; Waslurachim Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The objective of this study was to figure out whether there is any correlation between students’ motivation and English learning achievement at Grade XI Madrasah Aliyah Negeri 1 Kota Bengkulu. In this research, the researcher used Correlational research in a quantitative design. In correlational method, the researcher used the correlation statistical test to describe and measure between two variables. The population of this study was the whole students of XI grade MAN 1 Bengkulu City with total students 355. The researcher took all of population as the sample of the research. Therefore, the sample of this research was about 350 students at eleventh grade MAN Model Bengkulu. To obtain the data, the researcher used questionnaire and documentation as the instruments of this research. The questionnaire of students’ motivation was adopted from The Attitude / Motivation Test Battery by R. C Gardner cited in (Rafasah, 2019). Moreover, the students’ learning achievement was identified by collecting the students’ English score in UTS or UAS or daily test. After collecting and analyzing the data, the researcher found that the sign. (2-tailed) Pearson correlation = 0.00 > 0.05 which means that there was a correlation between students’ motivation and English learning achievement at XI A students of SMAN 1 Kota Bengkulu. The researcher suggested for English teachers in developing some strategies to facilitate the students to have a good motivation. The researcher also suggested for the students to be more active in practicing English even though this research findings showed that the students’ motivation was good. Keywords: The Correlation, Students’ Motivation, English Learning Achievement